Anemia and Cancer Survival, A Peruvian study with a 5-year follow-up: Anemia y supervivencia del cáncer, Un estudio peruano con seguimiento de 5 años - Garcia Arispe, Jennyfer E. (2020)
Introduction: Anemia is a serious public health. Several studies indicate that anemia status is a factor that might influence survival and response to cancer treatment in patients. Objective: To determine the relationship between anemia and 5-year survival in cancer patients. Methods: Observational, analytical, and retrospective cohort study. The sample population consisted of novel diagnosed cancer patients registered for hospital care with their respective follow up from 2014 until 2019. Time to death, presence of anemia, and other variables were evaluated. Survival was determined using Kaplan Meier curves and analyzed using the log-rank test. Hazard ratio and risk were determined in turn using the Cox regression model. Results: 72 patients were included in the study, 79.2% of which correspond to solid neoplasms. Anemia was present at the time of diagnosis in 45.8% of patients. Statistically significant differences were found on survival curves for anemia, severity graded anemia, age, and clinical stage. Anemia showed a significant relation with survival (HR: 3.03; CI: 95; p <0.05) on the adjusted bivariate and multivariate analysis for age over 70 years. Likewise, on the respective adjusted analysis for age and clinical stage, anemia showed a significant relation with survival on patients with solid neoplasms. Overall, 30.3% of patients received some type of treatment for anemia. Conclusion: Anemia is frequently found in cancer patients and is significantly related to 5-year overall survival. Age over 70 and severe anemias were related to higher mortality of cancer patients